Screening Gangguan Mental Emosional: Depresi, Ansietas, Stres Menuju Sehat Jiwa Pada Mahasiswa Keperawatan Semester I Di Salah Satu Sekolah Tinggi Ilmu Kesehatan Yogyakarta 2020 - Kurniawan, Erik Adik Putra Bambang; Ngapiyem, Ruthy (Jurnal Kesehatan, 2020)
ABSTRACT Background: The process of transition from High School to Higher Education is a period that is not easy for some first semester students, need self-skills in preparation for a new environment in Higher Education. This adjustment will be a problem for students who are not as expected, thus increasing mental emotional problems. To find a picture of emotional mental problems that can be done by screening using the DASS 42 instrument. Objective: To find a picture of the problem of mental emotional disorders: depression, anxiety, and stress based on the results of screening for mental emotional disorders to reach mental health students. Method: The research design in this study is a descriptive survey research method to describe the problem of mental emotional disorders of respondents. Results: From a total of 141 respondents, the number of respondents who experienced depression problems was 42 respondents (30%) divided into mild depression categories 25 respondents (18%), moderate depression 13 respondents (9%), and severe depression 4 respondents (3% ). Respondents with anxiety problems were 94 respondents (67%) who were divided into mild anxiety categories 25 respondents (18%), moderate anxiety 48 respondents (34%), severe anxiety 16 respondents (11%), and very severe anxiety 5 respondents (4 %). While respondents who experienced stress were 28 respondents (20%) who were divided into mild stress categories 19 respondents (13%), moderate stress 6 respondents (4%), and severe stress 3 respondents (2%). Conclusion: Based on the results of screaning, respondents have emotional mental disorders in the form of depression, anxiety, and stress. Suggestion: Academic advisers to be able to improve mentoring and monitoring related to mental emotional disorders in students. Keywords: Screaning, Emotional Mental Disorders, Mental Health